Pengaruh Penambahan MgO dan SiO2 Serta Suhu Sintering Terhadap Sifat Fisis dan Mekanis Komposit Keramik α–Alumina - Jarot Raharjo (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
High mechanical properties of Alumina ceramic composites for armor materials have been developed using the additives SiO2and MgO. The percentage of additive MgO were 0,8 wt.%; 1 wt.%; 1,2 wt.% and the percentage of SiO2 was 1 wt.% in each composition of MgO. Various temperature sintering used in this research were 1500, 1550, and 1600oC. The powders were prepared by using wet milling method and ethanol used as a solution in a plenetary ball mill. The green body was pressed at 12 metric ton of pressure. The shrinkage, density, porosity, hardness and fracture toughnes of the sintered pellets were measured, and the microstructure of fractures pellets was observed by SEM. This research found that the optimum parameter obtained by adding SiO2 and MgO at sintering temperature 1600oC.